2013
DOI: 10.1063/1.4794838
|View full text |Cite
|
Sign up to set email alerts
|

Energy band alignment of atomic layer deposited HfO2 on epitaxial (110)Ge grown by molecular beam epitaxy

Abstract: . K.; Zhu, Y.; Maurya, D.; et al., "Energy band alignment of atomic layer deposited HfO2 on epitaxial (110)Ge grown by molecular beam epitaxy," Appl. Phys. Lett. 102, 093109 (2013); http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…This suggests that a robust interface prevents the oxidation of the (110)Ge surface similar to the case of HfO 2 on (110)Ge. 1 It has been reported that band offsets in addition to substrate orientation and surface structure can also depend on various other parameters such as overlayer crystallinity, deposition temperature, deposition rate, microscopic interface dipole and interdiffusion or reactivity. 40 However, in the case of amorphous BTO/(110)Ge, the surface reconstruction has the dominant effect as compared to the other variables.…”
Section: Energy Band Alignment Of Batio 3 On (110)gementioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that a robust interface prevents the oxidation of the (110)Ge surface similar to the case of HfO 2 on (110)Ge. 1 It has been reported that band offsets in addition to substrate orientation and surface structure can also depend on various other parameters such as overlayer crystallinity, deposition temperature, deposition rate, microscopic interface dipole and interdiffusion or reactivity. 40 However, in the case of amorphous BTO/(110)Ge, the surface reconstruction has the dominant effect as compared to the other variables.…”
Section: Energy Band Alignment Of Batio 3 On (110)gementioning
confidence: 99%
“…1,10,13,15,16,[42][43][44] However, the measures must be taken in order to compensate the positive changes generated during XPS measurement. [42][43][44][45] Unless, these positive charges were neutralized during the XPS measurement by flowing electron through the sample, there could be positive charge accumulation over the surface and potentially affect the band bending due to insufficient compensation of electron loss.…”
Section: Energy Band Alignment Of Batio 3 On (110)gementioning
confidence: 99%
See 2 more Smart Citations
“…[6,7] Moreover, HfO 2 is also used as a sensitive layer in Ion Selective Field Effect Transistors. [8] Several deposition techniques such as electron beam evaporation, [9] molecular beam epitaxy, [10] atomic layer deposition, [11] sol-gel process, [12] pulsed laser deposition, [13] and sputtering, [14] have been employed to form HfO 2 layers. Among these methods, the reactive magnetron sputtering provides more advantage in controlling the structure and composition of the deposited films.…”
Section: Introductionmentioning
confidence: 99%